Agricultural research in Southern Africa : a framework for action - Spurling, A. T. (Washington, D.C. : World Bank, 1992)
The objective of this framework for action is the development of a strategic agenda for the SADCC region that will strengthen the National Agricultural Research Systems (NARSs) of the member states.
Includes bibliographical references: p. 58-61.
hza 01/02/2019
Loans
Keywords: Agriculture; National agricultural research systems